Examining Interviewers' Ratings of Respondents' Health: Does Location in the Survey Matter for Interviewers' Evaluations of Respondents?. (13th October 2021) - Garbarski, Dana; Schaeffer, Nora Cate; Dykema, Jennifer
Abstract: Interviewers' ratings of survey respondents' health (IRH) are a promising measure of health to include in surveys as a complementary measure to self-rated health. However, our understanding of the factors contributing to IRH remains incomplete. This is the first study to examine whether and how it matters when in the interview interviewers evaluate respondents' health in a face-to-face survey, in an experiment embedded in the UK Innovation Panel Study. We find that interviewers are more likely to rate the respondent's health as "excellent" when IRH is rated at the end of the interview compared to the beginning. Drawing from the continuum model of impression formation, we examined whether associations between IRH and relevant covariates vary depending on placement in interview. We find that across several characteristics of interviewers and respondents, only the number of interviews completed by interviewers varies by IRH assessment location in its effect on IRH. We also find evidence that interviewer variance is lower when IRH is assessed prior to compared to after the interview. Finally, the location of IRH assessment does not impact the concurrent or predictive validity of IRH. Overall, the results suggest that in a general population study with some health questions, there may be benefits to having interviewers rate respondents' health at the beginning of the interview (rather than at the end as in prior research) in terms of lower interviewer variance, particularly in the absence of interviewer training that mitigates the impact of within-study experience on IRH assessments.